MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS III MELALUIPENERAPAN METODE PEMBELAJARAN EXAMPLES NON EXAMPLESDI SDN 010 BAYAS JAYA - Masdar (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This research was a classroom action research aiming to improve students' learning outcomes and speaking skills through the Examples Non Examples method. This research was conducted at grade III of SDN 010 Bayas Jaya, Indragiri Hulu. The subjects in this research were 28 third-grade students of SDN 010 Bayas Jaya. The research results obtained that the percentage of students' speaking skills after implementing the Example Non-Example method in the second cycle was 86.75% or classified as